IDENTIFIKASI STRESSOR AKADEMIK PADA MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI ANGKATAN 2021 - Kusaini, Utami Niki; Thohiroh, Nazila Syifa; Khasanah, Umi Laelatul; Amelia, Resni; Permadi, Kimas; Maharani, Auffa; Simar, Simar; Ayuningtias, Eka Wahyu (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
In general, academic stress can be said as stress that comes from academic activities, academic stress has a variety of negative impacts, such as decreased academic achievement, procrastination, health problems, sleep disorders (insomnia), smartphone addiction, suicide and others. According to the theory (Heiman & Kariv, 2005) Stress is caused by certain things, one of which is stress that occurs in students, namely stress that comes from within the individual, such as physical conditions, motivation, and the type of personality of the student himself, while those that come from outside the individual, such as family, work, facilities, environment, lecturers, and others. Researchers found problems related to the identification of academic stressors in third-year students, there are students who are burdened because of too many exams, students get an excessive load of lecture assignments, declining academic achievement, there are students who are unable to manage lecture time and organizations on campus. The purpose of this study was to identify academic stressors in third-year students of the Faculty of Teacher Training and Education, Jambi University. The research method used in this research is descriptive qualitative research. Discussing the identification of academic stressors, this involved several students who became sources with the criteria of feeling stress about the world of lectures, which can be concluded that the cause of stress symptoms is felt because of the many demands of lecture assignments, fear of failure, overthinking with lectures, and ultimately can cause academic stress in students.